Sport can do better: female athletes' perspectives on managing menstrual and hormonal contraceptive cycle-related symptoms - Chica-Latorre, Sara; Knight-Agarwal, Catherine; McKune, Andrew; Minehan, Michelle (Frontiers in Sports and Active Living, 2025)
IntroductionMenstrual cycle-related symptoms (MCS) affect female athletes' wellbeing, quality of life, sports participation, and performance. Hormonal contraceptives (HCs) moderate hormone activity, but do not necessarily alleviate MCS. Recent research indicates no significant effect of the MC or HC cycle on measurable performance, yet perceived effects on performance and wellbeing remain noticeable. Thus, this study aimed to understand how female athletes are impacted by and manage MCS, and how they want these symptoms addressed in sporting contexts.MethodsUsing a constructivist paradigm approach, experiences and perspectives of 30 female athletes [aged 19–32, 18 naturally cycling (NC) and 12 using HCs] from 17 sports were gathered through semi-structured interviews and analysed using reflexive thematic analysis.ResultsFour main themes were identified: (1) significant impacts of MCS on athletes, (2) perceived functional difference when MCS are present, (3) uncertainty about the effectiveness of management strategies despite trying multiple options, and (4) a desire for a supportive sport environment with meaningful discussions about MCS, though there is reticence.DiscussionThese findings highlight the need to view MCS as more than a minor inconvenience, consider athletes' perceptions, and pursue more research on evidence-based management options and MC culture change in sports. Regardless of the sport, it is crucial to advocate for athlete-centred training loads and schedules that can improve the overall experience of athletes enduring MCS, helping them continue to participate in sport and perform at their best.